Penegakan Hukum Pidana Berbasis Keadilan Sosial Terhadap Nelayan Lokal Pelaku Tindak Pidana Illegal Fishing di Zona Eonomi Eksklusif Indonesia - Arsafina Paka; Riska Andi Fitriono (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
The current criminal law policy for illegal fishing in the Exclusive Economic Zone provides different sanctions between local fishermen and foreign fishermen, giving rise to social impacts, namely injustice for local fishermen. This research aims to examine the current illegal fishing criminal law policy and then review it from social justice theory to seek justice for local fishermen in terms of imposing sanctions. This research uses normative legal research with a statutory approach and a conceptual approach. The research results show that current criminal law policies still do not fulfill the concept of social justice in law enforcement. In the context of social justice theory, we must pay attention to the principle of equality So both local fishermen and foreign fishermen should be involved illegal fishing have the same rights, obligations and position before the law. Efforts to implement bilateral agreements and prioritize administrative sanctions can achieve social justice for local fishermen.